Hollow nanotubes carbon@tellurium for high-performance Al-Te batteries - Li, Zhanyu; Lv, Wenrong; Wu, Gaohong; Zhang, Wenming (Electrochimica acta, 2022)
In Al-Te batteries, the dissolution of tellurium and tellurium chloroaluminate compounds during the electrochemical reaction will seriously affect its electrochemical performance. In order to avoid this problem, we prepared hollow nanotube carbon-coated tellurium electrode materials, whose coating will increase electronic conductivity and avoid the collapse of structure caused by volume expansion during charging and discharging. The most important thing is that the dissolution of the tellurium and tellurium chloroaluminate compounds is greatly reduced due to the presence of the carbon coating. In addition, the results of density functional theory (DFT) show that AlCl4− has a large adsorption energy and a low diffusion barrier on Te (101) surface, which makes it exhibits excellent electrochemical performance. Its first discharge specific capacity is 1131.9 mAh g−1 at 200 mA g−1 and the initial discharge voltage is about 1.45 V. In addition, after 1000 cycles, the discharge specific capacity is still 254.2 mAh g−1 at 500 mA g−1. Interestingly, the electrochemical performance of hollow nanotubes carbon-coated tellurium is superior to that the related aluminum-based batteries recorded in the literature. Therefore, our work will lay a certain experimental and theoretical basis for the optimization of charging and discharging performance of Al-Te and other related secondary rechargeable batteries. [Display omitted]